A Survey of Removable Partial Denture (RPD) Retentive Elements in Relation to Type of Edentulism and Abutment Teeth in Commercial Laboratories in Athens - Nick Polychronakis; Michael Sotiriou; Alcibiades Zissis (University of Zagreb. School of Dental Medicine, 2014)
Objective. The aim of this survey was to record removable partial denture (RPD) retentive elements and abutment teeth in partially edentulous patients, identified in commercial laboratories in Athens, Greece. Material and Methods. 628 master casts with the corresponding cast metal frameworks used in the construction of RPDs were evaluated. Casts were photographed to identify the number and position of existing teeth, the partial edentulism class and the retentive elements. Prevalence tables and the x2 test were used for the statistical analysis of the collected data (α=.05). Results. There were 276 maxillary (43.9%) and 352 (56.1%) mandibular casts. Maxillary edentulism entailed almost a total absence of right third molars in 96.7% and left third molars 96.0% of casts, with lower rates for the first and second molars. Edentulism in the posterior mandible presented a similar pattern. The most profound findings concerning retentive elements were: 91.9% of the retainers used were clasps and the remaining 8.1% were attachments. Of the clasps used, 48.9% were of the Roach Τ type, a finding more common in Kennedy Class I as compared to other Kennedy Classes (p<0.01). The circumferential clasps accounted for 19.3% of the total clasps used, and it was less frequently presented (8.8%) in Kennedy I Classes (p<0.01). Conclusions. Roach clasps were used in the majority of cases whereas RPI clasps and attachments were rarely used.